2014
DOI: 10.1016/j.molcel.2014.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Capture of Noncoding RNAs or Protein-Coding Genes by Herpesviruses to Alter Host T Cell Function

Abstract: SUMMARY In marmoset T cells transformed by Herpesvirus saimiri (HVS), a viral U-rich noncoding RNA, HSUR 1, specifically mediates degradation of host microRNA-27 (miR-27). High-throughput sequencing of RNA after crosslinking immunoprecipitation (HITS-CLIP) identified mRNAs targeted by miR-27 as enriched in the T-cell receptor (TCR) signaling pathway, including GRB2. Accordingly, transfection of miR-27 into human T cells attenuates TCR-induced activation of mitogen-activated protein kinases (MAPKs) and inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 52 publications
5
72
0
1
Order By: Relevance
“…Five months after birth, these mice started to develop autoimmune disorders that manifested in runting, failure to thrive, lymphadenopathy and splenomegaly, and lymphocytic tissue infiltration that was particularly severe in the lung, colon, and stomach (Supplemental Figure 1B and data not shown). Interestingly, regardless of the absence or presence of increased IFN-γ + T cell frequencies in younger or older CD4-Cre R27Tg mice, respectively ( Figure 1, A and B), we could consistently detect reduced IFN-γ production by miR-27-overexpressing T cells on a per-cell basis ( Figure 1C), supporting the previous notion that miR-27 functions as a potent repressor of IFN-γ in T cells (13,14).…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Five months after birth, these mice started to develop autoimmune disorders that manifested in runting, failure to thrive, lymphadenopathy and splenomegaly, and lymphocytic tissue infiltration that was particularly severe in the lung, colon, and stomach (Supplemental Figure 1B and data not shown). Interestingly, regardless of the absence or presence of increased IFN-γ + T cell frequencies in younger or older CD4-Cre R27Tg mice, respectively ( Figure 1, A and B), we could consistently detect reduced IFN-γ production by miR-27-overexpressing T cells on a per-cell basis ( Figure 1C), supporting the previous notion that miR-27 functions as a potent repressor of IFN-γ in T cells (13,14).…”
Section: Introductionsupporting
confidence: 86%
“…Moreover, our recent finding of elevated IFN-γ responses and lympho-hyperactivated phenotypes in mice harboring T cells with miR-27 overexpression further supported the conclusion drawn by the aforementioned study in patients with MS (11,12). Surprisingly, the role of miR-27 in driving IFN-γ-mediated Th1 autoimmune responses implicated by these 2 reports seems to be at odds with previous studies, in which miR-27 was shown to be a potent repressor of IFN-γ and T cell receptor-mediated (TCR-mediated) activation (13,14). The fact that overexpression of miR-27 in T cells resulted in impaired Th1 differentiation further suggested that miR-27-mediated gene regulation limits, rather than promotes, Th1 responses (12).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…44 HSUR-1 in HVS may be a little older. A homologous site within the same type of RNA element (HAUR-1) is found in a closely related rhadinovirus from spider monkeys, Herpesvirus ateles (HVA), 45 but not in other rhadinoviruses infecting Old World monkeys and apes. Squirrel monkeys and spider monkeys are both New world monkeys, and are thought to have shared a common ancestor around 20 Myr ago.…”
Section: Evolution Of Viral Regulators Of Mirnasmentioning
confidence: 99%
“…First, has miR-27 always played an antiviral role? In the case of HVS infection of T cells, Guo et al identified and validated miR-27 targets that are involved in T cell receptor (TCR) signaling, 45 a pathway which is activated in HVS-transformed human T cells. 47 While this particular pathway is unlikely to be relevant to MCMV, which does not infect T cells, it was also shown that miR-27 suppressed mitogen-activated protein kinase (MAPK) signaling and effector cytokines (IFN-g, IL-10) that are part of the cellular response to many viruses including MCMV.…”
Section: Evolution Of Viral Regulators Of Mirnasmentioning
confidence: 99%